Prognostic significance of incorporating SpO2 recovery time to the 6-minute walk test protocol and to a modified GAP index risk prediction model in patients with idiopathic pulmonary fibrosis - Yildirim, Elif; Tutus, Nisanur; Aydogdu, Yagmur; Ozmen, Ipek (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2026)
Background and aim: The prognostic potential of SpO2 recovery time recorded during 6-min walk test (6MWT) remains unexplored in the setting of idiopathic pulmonary fibrosis (IPF). This study aimed to investigate prognostic significance of cardiopulmonary recovery time after the 6MWT and the utility of a modified gender-age-physiology (GAP) index incorporating SpO2 recovery time instead of DLCO as a predictive model in IPF patients.Methods: A total of 64 patients with IPF (mean±SD age: 61±10.2 years, 79.7% were males) were included in this retrospective cohort study. Cardiopulmonary recovery time (SpO2 recovery time and heart rate recovery [HRR] time in seconds), GAP index (gender, age, forced vital capacity [FVC] and diffusion capacity [DLCO]) and modified GAP index (gender, age, FVC, SpO2 recovery time) scores were recorded.Results: SpO2 recovery time and modified GAP index predicted the increased risk of overall adverse events (OR 1.017, p=0.002 and OR 1.667, p160 s (AUC: 0.813, p3.5 (AUC: 0.762, p